Are We Experts?: Perspectives of Korean Teachers on their Careers in Infant and Toddler Care. Issue 1 (March 2014) - Park, Soyeon; Wee, Su-Jeong; Yang, Sungeun
THE PRESENT STUDY INVESTIGATES how Korean infant/toddler teachers define their role in centre-based childcare settings and how their attitudes and perspectives influence their professional identities and relationships with parents. The study utilised the interpretive science paradigm and individual interviews for data collection, and the qualitative data analysis method explored the experiences of 19 infant/toddler teachers. Participants defined their role as 'teacher as mother' and placed more emphasis on nurturing than educating despite their acknowledgement of the importance of the educational aspects of centre-based care. The consensus among infant/toddler teachers that it is best for mothers to care for children at home derives from 1) teachers' consideration of infants/toddlers' developmental characteristics, and 2) the limitations of centre-based programs to fulfill the developmental needs of infants and toddlers. This perspective affects their sense of professionalism and job satisfaction and can lower the quality of overall infant and toddler care.